8 channel serial controller for Remotely Operated Vehicle (ROV) applications - Zainah, Md. Zain; R. Badlishah, Ahmad; Mohd. Rizal, Arshad (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th-19th May 2005 at Putra Palace Hotel, Kangar.